PERAN GURU DAN ORANG TUA DALAM PENDIDIKAN KARAKTER ANAK USIA DINI - Rifdah Fauziah Ramandhini; Taopik Rahman; Purwati Purwati (Universitas Muhammadiyah Purwokerto, 2023)
In the 21st century, the decline of good character in adolescents is a challenge for parents and teachers. Parents anda teachers need to carry out their roles in early childhood character education. The formation of good character from an early age will affect the character of children as adults. Thus, there needs to be good cooperation between parents of students and teachers in early childhood character education. This study uses the method of literature study. The results of this study are the role of parents in religious character education, namely by using exemplary methods and giving good advice, parents also take their children to Al-Qur'an Study Place. In addition, parents also provide firm action to children so that children can hear advice from parents. Meanwhile, the role of the teacher ini character education is as a role model, facilitatorm and also a motivator. With this, it is hope that parents and teachers will be more aware of their role and the importance of character education in early childhood.